Reduced telomere length in amniocytes: an early biomarker of abnormal fetal development?. Issue 16 (4th March 2022) - Goumy, Carole; Veronese, Lauren; Stamm, Rodrigue; Domas, Quentin; Hadjab, Kamil; Gallot, Denis; Laurichesse, Hélène; Delabaere, Amélie; Gouas, Laetitia; Salaun, Gaelle; Perbel-Richard, Céline; Vago, Philippe; et al.
Abstract: Telomeres protect chromosome ends and control cell division and senescence. During organogenesis, telomeres need to be long enough to ensure the cell proliferation necessary at this stage of development. Previous studies have shown that telomere shortening is associated with growth retardation and congenital malformations. However, these studies were performed in newborns or postnatally, and data on telomere length (TL) during the prenatal period are still very limited. We measured TL using quantitative PCR in amniotic fluid (AF) and chorionic villi (CV) samples from 69 control fetuses with normal ultrasound (52 AF and 17 CV) and 213 fetuses (165 AF and 48 CV) with intrauterine growth retardation (IUGR) or congenital malformations diagnosed by ultrasound. The samples were collected by amniocentesis at the gestational age (GA) of 25.0 ± 5.4 weeks and by CV biopsy at 18.1 ± 6.3 weeks. In neither sample type was TL influenced by GA or fetal sex. In AF, a comparison of abnormal versus normal fetuses showed a significant telomere shortening in cases of IUGR (reduction of 34%, P < 10 −6 ), single (29%, P < 10 −6 ) and multiple (44%, P < 10 −6 ) malformations. Similar TL shortening was also observed in CV from abnormal fetuses but to a lesser extent (25%, P = 0.0002; 18%, P = 0.016; 20%, P = 0.004, respectively). Telomere shortening was more pronounced in cases of multiple congenital anomalies than in fetuses with a single malformation, suggesting a correlation between TL and the severity of fetal phenotype. Thus, TL measurement in fetal samples during pregnancy could provide a novel predictive marker of pathological development.